Law of monopolies, restrictive and unfair trade practices - Avtar Singh (Lucknow, 1993)
The Monopolies and Restrictive Trade Practices Act which started its life in 1969 has had a new dealing at the hands of the legislature. It did have a history of amendments even before, but the amendment of 1991, which is a part of the present wave towards economic liberlisation, is likely to generate far-reaching socio-economic forces of beneficial nature. The major thrust of the Act in its inception was control of monopoly houses. Monopolistic concentration of economic power was then measured for control purposes by two yardsticks. One of them was the command over assets whether self-owned or borrowed. Once the asset power reached a certain amount in terms of money, the undertaking would be identified as a monopoly under taking. It was required to register itself as an MRTP undertaking. It had then to undergo a process of sanctions if it wanted further growth by any method whatsoever. Partly because of the crippling effect of such dilatory and expensive sanctions and partly because of the linkage of the Act with the Industries (Development and Regulation) Act, 1951, which Act has been reduced to a minimal existence with only few items surviving on its schedule, the experiment of sanctioned growth of monopoly houses has been aban doned. Now they are free of the yokes of the MRTP Act to grow to any manageable extent. The other yardstick for identifying a monopoly house was trade power. Power over trade to a sizeable extent creates a position of market dominance. Such undertakings are known by the name of "dominant undertaking". A position of trade domination paves the way for imposition of monopolistic trade practices. Since the industrial and trade structure of the country has to be protected against such crippling practices, this part of the definition of a monopoly house has been retained in the Act, as also the power to order their sub-division or severance of interconnection. With the elimination of the provisions relating to the MRTP companies, the restrictions as to appointment of directors and acquisition of shares have also disap peared.
Keywords: MRTP Law